2020
DOI: 10.1371/journal.pntd.0008761
|View full text |Cite
|
Sign up to set email alerts
|

Health state utility values in people living with HTLV-1 and in patients with HAM/TSP: The impact of a neglected disease on the quality of life

Abstract: Background: HTLV-1 is a neglected sexually transmitted infection despite being the cause of disabling neurological disease HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). There is no treatment for this infection and public health policies are essential to reduce its transmission. However, there are no data to support adequate cost-effective analysis in this field. The aim of this study was to obtain health state utility values for individuals with HAM/TSP and HTLV-1 asymptomatic carriers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
1
30
0
2
Order By: Relevance
“…It is the causative agent of a severe form of blood cancer called adult T-cell leukaemia/lymphoma (ATLL) 2 and a range of debilitating neuromuscular disorders—HTLV-associated myelopathy/tropical spastic paraparesis (HAM/TSP) 3 , which often lead to paralysis. Although only 5–10% of the estimated 10–20 million people 4 infected with HTLV-1 worldwide will develop ATLL 2 , a recent report showed that the vast majority of otherwise asymptomatic patients suffer from issues that severely impact their quality of life, including pain, discomfort and depression 5 . 12.7% of HAM/TSP patients reported their quality of life was worse than death 5 , based on the Euroqol five dimension questionnaire (EQ-5D).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the causative agent of a severe form of blood cancer called adult T-cell leukaemia/lymphoma (ATLL) 2 and a range of debilitating neuromuscular disorders—HTLV-associated myelopathy/tropical spastic paraparesis (HAM/TSP) 3 , which often lead to paralysis. Although only 5–10% of the estimated 10–20 million people 4 infected with HTLV-1 worldwide will develop ATLL 2 , a recent report showed that the vast majority of otherwise asymptomatic patients suffer from issues that severely impact their quality of life, including pain, discomfort and depression 5 . 12.7% of HAM/TSP patients reported their quality of life was worse than death 5 , based on the Euroqol five dimension questionnaire (EQ-5D).…”
Section: Introductionmentioning
confidence: 99%
“…Although only 5–10% of the estimated 10–20 million people 4 infected with HTLV-1 worldwide will develop ATLL 2 , a recent report showed that the vast majority of otherwise asymptomatic patients suffer from issues that severely impact their quality of life, including pain, discomfort and depression 5 . 12.7% of HAM/TSP patients reported their quality of life was worse than death 5 , based on the Euroqol five dimension questionnaire (EQ-5D).…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-1–associated myelopathy (HAM) is a debilitating condition that results from an inflammatory response mainly within the spinal cord, but with increasing evidence of widespread brain inflammation. HAM greatly impacts patient’s autonomy and quality of life, and, during follow-up, about 50% become wheelchair dependent [ 3 6 ]. In Brazil, the risk of HAM and other neurological diseases is reported to be higher than usual at 5% [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 The clinical course, although diverse, from mildly impaired mobility after decades to wheelchair dependency in weeks, greatly affects the patient's autonomy and quality of life. 3 Some asymptomatic individuals also have discreet neurologic signs suggesting limited CNS damage. 4 Cognitive dysfunction and encephalitis have also been reported with HTLV-1, indicating that the damage is not restricted to the spinal cord.…”
mentioning
confidence: 99%